Penerapan Metode Bercerita Dalam Menanamkan Nilai-Nilai Karakter Pada Anak Usia Dini - Ivonne Hafidlatil Kiromi (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2021)
Abstract Storytelling is an activity that is carried out by one person orally to another with tools or without tools about what must be conveyed in the form of messages, information or just a fairy tale to be heard with a sense of fun because the person who presents the story conveys it interestingly. Storytelling is a universal communication method that greatly affects the human psyche. Even the biblical texts also contain many stories. In addition, folk stories given to children are able to increase their knowledge about the culture, values, and traditions of various different community groups in various regions of the world, the storytelling method is also one of the methods that educators or parents can use in instilling values. character values ​​in children. character is a reflection of the attitude of each individual that can be observed directly. If the child shows a good attitude towards himself and others, it will be said to have a good character. However, if the child behaves otherwise, the surrounding environment will judge it with a negative character. Therefore, in order for a child to be able to have a good character until adulthood, character formation from an early age is needed Keywords: Storytelling method, character values